Experimental evaluation of the dry coal deshaling by pneumatic vibrating FGX separator on the CO2 gasification process. (4th November 2020) - Czerski, Grzegorz; Grzywacz, Przemysław; Dziok, Tadeusz; Śpiewak, Katarzyna; Makowska, Dorota
Summary: The dry deshaling process using the FGX method is a modern technique of coal quality enhancing without the use of water. The positive effect of this operation is the increase of calorific value and the removal of contaminants such as sulphur, chlorine, mercury and other heavy metals along with the separated gangue. However, elements such as sodium, potassium or calcium, considered as catalysts in the gasification process, are also partially removed. Consequently, the global effect of the dry deshaling on coal reactivity, being a key parameter determining its suitability for the gasification, is hard to predict. This study aims to determine the impact of dry deshaling of coal by FGX separator on its reactivity. Using TG analysis, 10 samples of coals from Polish mines, before and after the dry deshaling at commercially working FGX separator, were gasified in CO2 atmosphere under non‐isothermal conditions. The effect of deshaling on the basic properties of coals, ash composition and the content of contaminants such as sulphur and mercury, was also determined. The results showed slightly lower reactivity of clean coals. The values of kinetic parameters of gasification reaction were similar, or an increase in the activation energy value was compensated by the higher value of the pre‐exponential factor. The basic properties of coals and the content of sulphur and mercury have changed after the deshaling process, and the magnitude of these changes differed significantly among the samples analysed. The changes in the ash composition were insignificant. These results suggest that FGX technology may be an attractive way of coal preparing for the gasification, resulting in a reduction of by‐products and contaminants without adverse effect on coals reactivity.